Two Seventeenth-Century Garden Views from the Royal Palace of Aranjuez - Marianna S. Simpson; Richard L. Kagan (Boletín del Museo del Prado)
Around 1660 the artist Benito Manuel Agüero completed thirty-three paintings for the «Salón» of Philip IV’s palace at Aranjuez. This pictorial program included seven large over window (sobreventana) paintings, of which five have long formed part of the collections in the Museo del Prado. The other two sobreventanas, depicting garden scenes of the Buen Retiro and El Pardo, were separated from the set, apparently in the early 19th century, and are discussed here for the first time.